Estudo experimental da ligação de placas de compensado estrutural com perfis do sistema construtivo Light Steel Framing - Janaína Costa Rezende (2019)
The self-supporting construction system, consisting of the galvanized cold-formed profiles, known worldwide as Light Steel Framing, it has been gaining a place in the Brazilian civil construction scenario. Therefore, this research has as main objective to investigate, by mean a theoretical and experimental study, the behavior of the connection of the structural plywood with the Light Steel Framing profiles system, with the intention of using such boards in the shear wall of the system. During the tests it was considered the anisotropy and the asymmetry of the wood. 92 structural plywood specimens were tested to determine, by means of flexure tests, the modulus of elasticity and the rupture stress of the structural plywood boards and 144 specimens to evaluate the connecting behavior between self-tapping screws and the structural plywood boards fixed in the Light Steel Framing profiles system, by means of the push test. The results showed that the specimens formed by 18,3 mm structural plywood boards, with longitudinal cutting in the boards in relation to the external fibers of the board, in other words, when the cutting is parallel to the 2440 mm length of the plywood, showed higher static flexural strength in relation to the 11,1 mm boards and transverse cutting in the boards. In addition, in push test, the specimens that contained longitudinal cutting in the boards, 18,3 mm boards and 0,80 mm steel profiles exhibited greater connection stiffness. While the specimens with 11,1 mm boards, 0,95 mm steel profiles and also longitudinal cutting in the boards showed the highest maximum force per screw. These results will contribute to studies about the reduction of steel in the shear wall of this system, commonly made with strips and steel profiles galvanized, taking into account the likely efficiency of the plywood as a structural component, especially in buildings of social interest (low cost construction). Furthermore, this study will contribute to the national standardization on the subject studied, the diffusion of technical knowledge about this system and a more sustainable construction.